Molecular modeling of corrosion processes : scientific development and engineering applications - Taylor, Christopher D., 1978-; Marcus, P. (Philippe), 1953- (Electrochemical Society series., 2015)
Presents opportunities for making significant improvements in preventing harmful effects that can be caused by corrosion -Describes concepts of molecular modeling in the context of materials corrosion -Includes recent examples of applications of molecular modeling to corrosion phenomena throughout the text -Details how molecular modeling can give insights into the multitude of interconnected and complex processes that comprise the corrosion of metals -Covered applications include diffusion and electron transfer at metal/electrolyte interfaces, Monte Carlo simulations of corrosion, corrosion inhibition, interrogating surface chemistry, and properties of passive films -Presents current challenges and likely developments in this field for the future.